2018
DOI: 10.1037/fam0000432
|View full text |Cite
|
Sign up to set email alerts
|

“The family that prays together . . .”: Relational processes associated with regular family prayer.

Abstract: In the present article we explored how family prayer reportedly influenced family relationships. We conceptualized family prayer as a family ritual in religious families and used a qualitative methodology to interview a religiously, ethnically, and geographically diverse sample of 198 families ( = 476). Analysis of data revealed 7 related themes. Family prayer served important functions and influenced relationships in various ways including (a) as a time of family togetherness and interaction; (b) as a space f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 53 publications
1
23
0
2
Order By: Relevance
“…Empirical work on family rituals has offered additional insight. Although family ritual typically benefits individuals and relationships (Chelladurai et al 2018;Fiese et al 2002;Marks and Dollahite 2012), additional empirical support for the danger of excessive religious rigidity is offered by a study that found that compulsory family worship was more detrimental than no family worship at all (Lee et al 1997). It appears possible that a major cause of parent-parent and parent-child conflict over religious matters may stem from unhealthy levels of firmness (rigidity) and/or unwillingness to manifest appropriate kinds of flexibility in religious belief, practice, and ritual.…”
Section: Intergenerational Transmission Of Religionmentioning
confidence: 99%
“…Empirical work on family rituals has offered additional insight. Although family ritual typically benefits individuals and relationships (Chelladurai et al 2018;Fiese et al 2002;Marks and Dollahite 2012), additional empirical support for the danger of excessive religious rigidity is offered by a study that found that compulsory family worship was more detrimental than no family worship at all (Lee et al 1997). It appears possible that a major cause of parent-parent and parent-child conflict over religious matters may stem from unhealthy levels of firmness (rigidity) and/or unwillingness to manifest appropriate kinds of flexibility in religious belief, practice, and ritual.…”
Section: Intergenerational Transmission Of Religionmentioning
confidence: 99%
“…В качестве таких действий информанты называли просмотр фильмов или диафильмов, подготовку к праздникам, приемы пищи, молитвы, чтение вслух, настольные игры. Наиболее значимы для семьи повторяющиеся способы такого времяпрепровождения, то есть семейные традиции (ритуалы), способствующие формированию чувства семейной совместности [Chelladurai et al, 2018]. «Все мы идем в храм, приходим, обедаем все вместе, и кто-то, ну, естественно, кто-то у нас, папа отдыхает немножечко, потому что он сразу тоже, кто-то ходит гулять, кто-то дома, занимается какими-то делами.…”
Section: семейное времяunclassified
“…In a more recent study which examined the role of family prayer and various relational processes it was found that families who engaged in regular prayer time together also saw this time and space as an opportunity of family togetherness and interaction, a space for social support, and a means for the intergenerational transmission of religion and values (Chelladurai et al 2018). It was also found that families would use this time to address issues and concerns, which contributed to reduced relational tensions and increased feelings of connectedness, unity, and bonding (Chelladurai et al 2018). Interestingly, Chelladurai et al (2018) also found that family prayer or the lack thereof was also a potential barometer for family disunity.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that families would use this time to address issues and concerns, which contributed to reduced relational tensions and increased feelings of connectedness, unity, and bonding (Chelladurai et al 2018). Interestingly, Chelladurai et al (2018) also found that family prayer or the lack thereof was also a potential barometer for family disunity. Thus, outcomes from these studies demonstrated consistent positive benefits of family worship and family prayer in the areas of family connection, adolescent behavior, child well-being and religious commitment (Chelladurai et al 2018;Dudley et al 1987;Erickson 1992;Strahan 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation